LABORATORY EVALUATION OF BENGKULU ISOLATES OF Beauveria bassiana AND Metarhizium anisopliae AGAINST COFFEE BERRY BORER, Hyphotenemus hampei, USING SPRAYING METHOD - Apriyanto, Dwinardi; ., Nadrawati (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2019)
Laboratory Evaluation of Local Isolates of Beauveria bassiana and Metarhizium anisopliae against Coffee Berry Borer, Hyphotenemus hampei, using spryaing method. Beauveria bassiana Bals (Vuillemin) and Metarhizium anisopliae (Metschnikoff) Sorokin are two species of fungi that have been studied widely and used as biological control of various insect pests, including coffee berry borer (CBB), Hyphotenemus hampei Ferrari. Laboratory studies were done in June – July 2017, to evaluate local isolates of both fungi species against CBB, the most destructive insect pest of coffee worldwide, including in Indonesia. B. bassiana was isolated from dead sweet potato weevil (Cylas formicarius) and green stink bug (Nezara viridula), and from soil. M. anisopliae was isolated from soil. The pure cultures of the fungi were mass-cultured on corn based media. The conidia harvested from 4 week colonies was hand sprayed directly upon CBB adults (females) and damaged coffee berry at the concentration of 109 ml-1. In additions, the conidia of B. bassiana isolated from C. formicarius alone was diluted to 106- 109 ml-1 and applied to damaged coffee berry. The results showed that when the conidia were applied directly upon the insects, the mortality of beetle were higher in B. bassiana than in M. anisopliae treatments. Pooled data indicated that B. bassiana isolated from death insects significantly caused higher mortality than did M. anisopliae isolated from soil. Beetle mortality was 76.7 and 80.0% for B. basiana, and 60.3 and 60% for M. anysopliae treatments. Application upon damage coffee berry indicated much lower mortality. Application of higher concentration upon damaged coffee berry resulted higher mortality, but data are not consistent. The mortality of CBB larvae was much less and negligible even at the highest conidia concentration.